Role of the IL-23/IL-17 Pathway in Rheumatic Diseases: An Overview - Schinocca, Claudia; Rizzo, Chiara; Fasano, Serena; Grasso, Giulia; La Barbera, Lidia; Ciccia, Francesco; Guggino, Giuliana (Frontiers in Immunology, 2021)
Interleukin-23 (IL-23) is a pro-inflammatory cytokine composed of two subunits, IL-23A (p19) and IL-12/23B (p40), the latter shared with Interleukin-12 (IL-12). IL-23 is mainly produced by macrophages and dendritic cells, in response to exogenous or endogenous signals, and drives the differentiation and activation of T helper 17 (Th17) cells with subsequent production of IL-17A, IL-17F, IL-6, IL-22 and tumor necrosis factor α (TNF-α). Although IL-23 plays a pivotal role in the protective immune response to bacterial and fungal infections, its dysregulation has been shown to exacerbate chronic immune-mediated inflammation. Well-established experimental data support the concept that IL-23/IL-17 axis activation contributes to the development of several inflammatory diseases, such as Psoriasis, Psoriatic Arthritis (PsA), Ankylosing Spondylitis (AS), Inflammatory Bowel Disease (IBD), Rheumatoid Arthritis (RA), Sjogren Syndrome (SS), and Multiple Sclerosis (MS). As a result, emerging clinical studies have focused on the blockade of this pathogenic axis as a promising therapeutic target in several autoimmune disorders; nevertheless, a greater understanding of its contribution still requires further investigation. This review aims to elucidate the most recent studies and literature data on the pathogenetic role of IL-23 and Th17 cells in inflammatory rheumatic diseases.